Classifications and Characteristics of Marine Heatwaves in the Northern South China Sea - Wang, Yinxia; Zeng, Jisheng; Wei, Zheng; Li, Shan; Tian, Song; Yang, Fan; Chen, Qidong; He, Yinghui (Frontiers in Marine Science, 2022)
The classifications and associated characteristics of marine heatwaves (MHWs) in the northern South China Sea (SCS) have been investigated. Based on the ratio of the area with MHWs to the total area of the northern SCS, the MHWs are divided into three categories, i.e., narrow coverage, moderate coverage, and wide coverage. Different kinds of MHWs (i.e., narrow coverage, moderate coverage, and wide coverage) contribute around 64, 28, and 8% to the total days with MHWs, respectively. Narrow coverage MHW scatters over the northern SCS continental shelf, and moderate (wide) coverage MHWs are concentrated east of Hainan Island (mid of northern SCS continental shelf). Wide coverage MHWs contribute more than 50% to the total MHW cumulative sea surface temperature (SST) anomalies. The cumulative days and temperature anomalies of all kinds of MHWs exhibit significant long-term trends and decadal variability.